Perception of tea sector officers on banning chemical fertilizer in the industry - Wijerathna, P.N.M.M.; Sandeepani, D.M.M.; Lakmali, M.G.T.; Samaraweera, G.C. (Colombo : Sri Lanka Association for the Advancement of Science, 2021)
Considering the lethal impacts of inorganic fertilizers, the Sri Lankan Government has banned inorganic fertilizers to promote organic fertilizers. However, the perception of ground-level people has not been considered before taking such a decision. Therefore, this study aims to explore the tea sector officials’ perception on this government decision, as they are also the growers and proprietors who are involved in the tea sector. The convenience sampling technique was used in selecting a sample of 30 officials who are actively involved in the tea sector. A Google form questionnaire was prepared and sent via emails to co lect primary data from tea sector officials. The five-point Likert Scale was used as the measurement technique and collected data were analyzed using Wilcoxon signed-rank test. According to the Wilcoxon signed-rank test, they carried a good perception regarding the timeliness (T=3.682; p=0.000) and feasibility of promoting organic fertilizer (T=4.893; p=0.000). However, their perception on the practicability (T=0.494; p=0.621), potential profitability (T=1.095; p=0.273), and strengthening Sri Lankan economy (T=1.505; p=0.132) were not significant (confidence level=0.05). However, officials deflected questions about the lack of availability, accessibility, increasing cost of production, and practicability in implementing the proposed decision. Furthermore, results revealed that the decision of promoting organic fertilizer may have a positive impact on society as well as on the environment. From a societal perspective, respondents revealed that promoting organic fertilizer will eventually result in creating new employment opportunities (T=4.428; p=0.000), reducing non- communicable diseases (T=4.696; p=0.000), earning extra income (T=4.681; p=0.000) and poverty reduction of the country (T=4.041; p=0.000). Moreover, the study revealed that the suggestion of the majority (43.3%) of the respondents is to continue tea cultivation with more organic and less inorganic fertilizers. The present study concluded that promoting organic fertilizer will be beneficial under specific circumstances such as enhanced availability. Hence, the findings of this study provide an overview for the Sri Lankan policymakers to become more concerned about banning chemical fertilizers outright and promoting organic fertilizer in Sri Lanka.
Keywords: Inorganic Fertilizer; Organic Fertilizer; Tea Sector Officials; Perception